Measurement of Viscosity of Gummy Fibre from Syzygium Cumini Seeds and Its Co- Relationship to the Mobility and Dialysability of Sugar Molecules by In Vitro Dialysis Studies - Agnihotri, Dr. Madhuri Akhilesh; Ambad, Ranjit S. (International Journal of Innovative Research in Medical Science, 2017)
Aim: 1. Measurement of Viscosity of Gummy Fibre from Syzygium Cumini Seeds and Its Co- relationship to the Mobility and Dialysability of sugar molecules by in Vitro Dialysis Studies. The effect of water soluble gummy fiber isolated from Syzygium Cumini seeds, Guargum and Gum Arabica on the mobility of glucose molecule across the dialysis bag was carried out. Hydrolysis of water soluble gummy fiber isolated from Syzygium Cumini seeds was conducted to identify the monosaccharide present in the hydrolysates by thin layer chromatography. Materials: The method and material used for isolation of water soluble gummy fibre isolated from Syzygium cumini seeds have been described. Viscosity of the water soluble gummy fibre isolated from Syzygium cumini seeds was determined by Ostwald’s Viscometer. Solution of 1% gummy fibre (w/v) isolated from Syzygium cumini seeds were prepared with distilled water at room temperature (250C). Viscosity was measured with the help of Ostwald’s Viscometer with respect to the flowing time and the density of the solution and results obtained were expressed in centipoise unit. Results: Increase in the hindrance of glucose mobility was observed with the increase in the amount of the gummy fibre as shown in the graph (Figure 1, 2, 3 & 4). The slow rate of dialysis of glucose in presence of guargum and gummy fibre from Syzygium cumini seeds may be attributed to viscosity of these fibers which in turn hinder the mobility and dialysability of glucose molecules. No hindrance in the mobility of the glucose molecule across the dialysis bag containing the gum arabica was observed as evident by the amount of glucose in dialysate which was almost equivalent to dialysate obtained from the dialysis bag containing glucose alone. Conclusion: The reduced mobility of glucose molecules caused by their entrapment in viscous gummy fibre across the dialysis bag in our study may be considered to be a crude representation of reduced intestinal absorption of highly viscous gel forming gummy fibers as reported carlier.